Pengaruh Fluktuasi Harga Emas, Tingkat Inflasi Terhadap Produk Gadai Emas Pada Bank Sumsel Babel Syariah - Anjeli Apriani; Maya Panorama (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the effect of gold price fluctuations and inflation rates on gold pawn products at the Islamic Sumatra Babel Bank for the period 2013-2019. This research includes quantitative research. The method used in this research is using multiple linear regression analysis method with a sample during the period 2013-2019 and using descriptive analysis techniques. The population and sample that will be used in this study are Bank Sumsel Babel Syariah in the 2013-2019 period.Financing that uses gold as a product object is highly dependent on fluctuations in gold prices. Islamic banks before providing financing to customers must make an assessment of the pawned gold. Based on the results of the study, it can be concluded: first, the results obtained from the calculations in this study are known that gold price fluctuations have a negative or no effect on the distribution of gold pawn financing and so is the second hypothesis that there is no effect of the inflation rate on the distribution of pawn products. gold bank sumsel babel sharia period 2013-2019.